Publisher Correction: Scaling of domain cascades in stripe and skyrmion phases - A. Singh (Nature Communications, 2019)
The original version of this Article contained an error in Fig. 4d, in which the label of the region to the left of the white dashed lines incorrectly read ‘Order stripes’. The correct version states ‘Disorder stripes’. This has been corrected in both the PDF and HTML versions of the Article.